The Influence of Chitosan Cross-linking on the Properties of Alginate Microparticles with Metformin Hydrochloride—In Vitro and In Vivo Evaluation - Szekalska, Marta (Molecules, 2017)
Sodium alginate is a polymer with unique ability to gel with different cross-linking agents in result of ionic and electrostatic interactions. Chitosan cross-linked alginate provides improvement of swelling and mucoadhesive properties and might be used to design sustained release dosage forms. Therefore, the aim of this research was to develop and evaluate possibility of preparing chitosan cross-linked alginate microparticles containing metformin hydrochloride by the spray-drying method. In addition, influence of cross-linking agent on the properties of microparticles was evaluated. Formulation of microparticles prepared by the spray drying of 2% alginate solution cross-linked by 0.1% chitosan was characterized by good mucoadhesive properties, high drug loading and prolonged metformin hydrochloride release. It was shown that designed microparticles reduced rat glucose blood level, delayed absorption of metformin hydrochloride and provided stable plasma drug concentration. Additionally, histopathological studies of pancreas, liver and kidneys indicated that all prepared microparticles improved degenerative changes in organs of diabetic rats. Moreover, no toxicity effect and no changes in rats behavior after oral administration of chitosan cross-linked alginate microparticles were noted.